CELEBRAÇÃO DE ACORDO DE NÃO PERSECUÇÃO PENAL EM CRIMES DE COLARINHO BRANCO: UMA ANÁLISE CRÍTICA - SANTOS, Laura Lyzandre Leão Nascimento dos (2023)
This work aims to conduct a critical analysis of the plea agreement in white-collar crimes. White-collar crimes are characterized by being committed by individuals of high social or economic status, involving illicit conduct in the economic, financial, or business fields. The research examines the plea agreement as a legal instrument that allows for the consensual resolution of criminal cases, avoiding the formal initiation of criminal proceedings. To do so, the criticisms and challenges related to the use of plea agreements in white-collar crimes are considered, such as the potential for excessive benefits to offenders, lack of transparency, and inequality in accessing this mechanism. Possible measures for improvement and regulation of this instrument are discussed, aiming to ensure greater effectiveness in holding criminals accountable and preventing these types of offenses. In conclusion, the plea agreement in white-collar crimes presents challenges and controversial points but can be a valid alternative to expedite justice and alleviate the burden on the criminal justice system. However, a broad debate and improvements in legislation and its implementation are necessary to ensure that the use of this instrument is effective, transparent, and aligned with the principles of justice and equity.